People with Multiple Sclerosis - Bull, Paul J. author. aut Link
XIV, 305 p.
Keywords: Multiple sclerosis is an incurable neurological disease of unknown cause with a fearful reputation for generating disability, unemployment, poverty and early death. This book critically surveys the current state of multiple sclerosis research, demonstrating the shortfall of current research undertaken on the lives of people with multiple sclerosis.